An evaluation of Tshivenḓa orthography of adoptives with special reference to Pan South African Language Board spelling rule booklets. Issue 2 (3rd May 2020) - Tshikota, Shumani Leonard; Musehane, Nelson Mbulaheni
Abstract : In Tshivenḓa, words which have been adopted from foreign languages have acquired entirely new characteristics. Such words have made a considerable contribution to the development of Tshivenḓa vocabulary. The aim of the article is to evaluate the role played by adoptives in Tshivenḓa orthography (spelling rules) and the challenges that arise as a consequence of the adoption of words. The methodology used is textual analysis, which entails a qualitative research methodology. Principles of the writing of adoptives have been extracted from the three Orthography and Spelling Rules booklets of Tshivenḓa approved by PanSALB, published respectively in 2005, 2008 and 2018. One of the rules states that Tshivenḓa words must follow the consonant-vowel pattern as indicated in the Orthography and Spelling Rules of Tshivenḓa published in 2005 and 2008. However, some of the adoptives in the 2018 booklet are written as pronounced in the original language and do not follow the open syllable system, for example Afrika, ḓresi and grisi . As a result, one finds that two different spellings exist for words, that is, according to the consonant-vowel pattern, or as pronounced in the original language, for example ḓiresi or ḓresi for English 'address' and ḓiraṱa or ḓraṱa for Afrikaans draad ('wire'). The current study notes the challenges brought about by adoptives and makes recommendations to address them.